A8.11 Rankl Expression is Lower on T and B Lymphocytes and Rankl+ Cells Tend to Accumulate in Circulation of Rheumatoid Arthritis Patients Treated with TNF Blockers. (25th February 2013) - Perpétuo, IP; Marques, R; Ponte, C; Canhão, H; Fonseca, JE
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is characterised by bone resorption and joint destruction. The receptor activator of NF-kB ligand (RANKL) plays a major role in bone loss because it is responsible for osteoclast differentiation and it is known that hyperactive immune system cells express surface RANKL. Several therapies commonly used for RA treatment have been shown to stop RA joint destruction. One of the hypothetical mechanisms explaining this effect could be an interference with the RANKL system. The aim of this work was to assess the effects of RA therapies in RANKL surface expression in different leukocyte populations by flow cytometry. Methods: Forty-nine patients diagnosed with RA were recruited for this study. Seventeen patients were naïve to any therapy, 14 were under methotrexate (MTX) – 8 of them at baseline of treatment with TNF blockers – and 18 patients were treated with TNF blockers. Blood was collected and total leukocytes were used for flow cytometry staining with anti human-CD66b for neutrophils, CD3 for T lymphocytes, CD19 for B lymphocytes and RANKL. Results: There were no differences regarding gender distribution, age, disease activity, C-reactive protein (CRP) levels or erythrocyte sedimentation rate (ESR). Patients treated with MTX or TNF blockers have reduced RANKL expression in neutrophils, T and B lymphocytes (p = 0.0027, p = 0.0003 and p = 0.0032, respectively) when compared to untreated patients. However the number of circulating RANKL + T and B lymphocytes was increased in patients treated with TNF blockers when compared to naïve patients (p = 0.0070 and p = 0.0183 respectively). No differences were found between groups regarding circulating number of leukocytes. We found no correlation of the studied parameters with CRP, ESR or DAS28. Conclusions: RANKL surface expression on T and B lymphocytes decreases and RANKL + cells tend to accumulate in the circulation of patients treated with TNF blockers. The reasons for this effect are not clear but might be related to disturbances induced by TNF blockage in gene expression, cell activation and migration.